EFL Students’ Perceptions of Activeness During the Implementation of Flipped Learning Approach at a Colombian University (GIST – Education and Learning Research Journal, 2018)
Flipped Learning is a pedagogical approach that provides students with more time in class to practice or to engage in dynamic tasks to promote active learning. Although the Flipped Learning research has become increasingly popular, limited research has been conducted in Colombia exploring students’ perceptions of this approach. This action research was carried out to explore students’ perceptions of activeness during the implementation of the Flipped Learning approach. The participants were 84 students from a state university in Colombia who were taking English as a complementary subject as part of their undergraduate degree programs. Students were exposed to this approach during a 16-week period in which they completed different pre-class, during-class, and post-class activities. Data collection instruments were designed based on the first three pillars of the approach: Flexible Environment, Learning Culture, and Intentional Content. Data were collected through immediate feedback, an online questionnaire, and a focus group interview, and were then analyzed in the light of these three pillars. The data indicated that students felt they were more engaged, their voices were heard, they felt increased ownership of their learning, and demonstrated a positive opinion towards collaborative work.
Keywords: Flipped Learning; Active Learning; Activeness; EFL; perceptions